Pengaruh Penerapan Absensi Fingerprint Terhadap Kedisiplinan Guru Di SDIT As-Sakinah Tanjungpinang - Uray Ferry Haryanto (Lembaga Pengembangan Kinerja Dosen, 2023)
Teacher discipline is an attitude or action that shows one's responsibility, professionalism, character, role model and personality in carrying out work as a teacher. In this case, teacher discipline refers to the teachers at SDIT As-Sakinah Tanjungpinang school. This study aims (1) to find out how the use of fingerprint attendance at SDIT As-Sakinah Tanjungpinang. (2) To find out how the discipline of teachers at SDIT As-Sakinah Tanjungpinang. (3) To find out how the effect of the application of fingerprint attendance on teacher discipline at SDIT As-Sakinah Tanjungpinang. The results of the study show that the Application of Fingerprint Attendance can be categorized as Very Good. This is evident from the results of the questionnaire data reaching 91.2% which is in the range of 81% - 100%. Teacher discipline can be categorized as Very Good. This is evident from the results of the questionnaire data reaching 88.7% which is in the range of 81% - 100%. The Effect of Fingerprint Attendance Application on Teacher Discipline at SDIT As – Sakinah Tanjungpinang the calculation results obtained that the value of rxy = 0.5419 was between the values (0.40 – 0.70). Thus, rxy = 0.5419 is greater than r table at a significant level of 5% and a significant level of 1% (0.5419 > 0.4629 > 0.3610). This means that Ha is accepted and Ho is rejected. So the results of the correlation analysis show that there is an effect of Fingerprint Attendance Application on Teacher Discipline at SDIT As - Sakinah Tanjungpinang.